2022
DOI: 10.1186/s12245-022-00429-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 outbreak on out-of-hospital cardiac arrest management and outcomes in a low-resource emergency medical service system: a perspective from Thailand

Abstract: Background The impact of the coronavirus disease 2019 (COVID-19) outbreak on out-of-hospital cardiac arrest (OHCA) has been of interest worldwide. However, evidence from low-resource emergency medical service systems is limited. This study investigated the effects of the COVID-19 outbreak on the prehospital management and outcomes of OHCA in Thailand. Methods This multicentered, retrospective, observational study compared the management and outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…While guidelines do not suggest avoiding intubation, some regions had protocols that prioritized the use of supraglottal airway devices ( 34 , 51 , 67 ). Rapid transport without intubation has also been recommended in some studies ( 73 ). The risk of infection during intubation may not be significantly higher when wearing personal protective equipment, but endotracheal intubation may have been avoided at front-line rescue sites due to a lack of studies on the risk of infection during intubation in the early stages of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While guidelines do not suggest avoiding intubation, some regions had protocols that prioritized the use of supraglottal airway devices ( 34 , 51 , 67 ). Rapid transport without intubation has also been recommended in some studies ( 73 ). The risk of infection during intubation may not be significantly higher when wearing personal protective equipment, but endotracheal intubation may have been avoided at front-line rescue sites due to a lack of studies on the risk of infection during intubation in the early stages of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of percutaneous coronary intervention reported by Ahn et al, Riyapan et al, and Phattharapornjaroen et al and the frequency of emergency coronary angiography reported by Sultanian et al did not show significant differences before and during the COVID-19 pandemic. Therefore, it can be assumed that the impact of the COVID-19 pandemic on the hospital-stage treatments of OHCA patients may be low; however, interpretation is limited because meta-analyses were not performed due to the small number of studies ( 34 , 71 , 73 , 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, another convincing explanation for decreasing the number of STEMI might be a higher incidence of fatal sudden cardiac arrest before hospital admission compared to the pre-pandemic era. Importantly, such disturbing outcomes were noted irrespective of the geographical location and in low-and high-income countries with well-developed healthcare systems [7,9,26,[29][30][31]. Furthermore, alarming data suggested a decrease in bystander CPR, utilization of AED, and a higher rate of non-shockable rhythms [1,7,9].…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with those of most previous studies [11][12][13], but a different trend has been reported in some Asian populations. For instance, Riyapan et al [14] reported no significant change in the occurrence of OHCA in public places in Thailand before and during the pandemic. Watanabe et al [15] also reported no decrease in the occurrence of OHCA in public places.…”
Section: Comparisons With Previous Studiesmentioning
confidence: 99%